Diversity of Ethiopian Fenugreek (Trigonella foenum-graecum L.) Accessions Based on Agromorphological Traits. (3rd November 2022) - Roba, Rameto; Mohammed, Wassu; Ruelle, Morgan; Tana, Tamado; Simion, Tariku
Abstract : Information on the diversity of landraces is necessary to improve crops through selection or hybridization. This study was conducted to show the diversity of fenugreek landraces and associated traits. A total of 160 accessions including one local and four improved standard checks were evaluated in an augmented block design at the Haramaya University research site in 2016. Data collected include days to flowering, days to maturity, seed yield (kg/ha), thousand seed weight (g), the number of primary branches, plant height at flowering (cm), the number of pods per plant, the number of secondary branches, average pod length (cm), the number of seeds per pod, and seed yield per plant (g/plant) of quantitative traits. The analysis of variance revealed the existence of significant differences between accessions of all parameters. Genotypic and phenotypic coefficients of variation departed from 5.95–56.91% and 6.47–58.88%. Heritability in the broad sense and expected genetic gain as percent mean varied from 60.9 to 96.1% and from 2.5 to 70.3%. The seed yield per plant, the number of secondary branches, and the number of pod per plant had positive direct effects on the yield at both genotypic and phenotypic levels and the number of primary branches, and the average pod length via seed yield per plant, while the number of seeds per plant through the number of primary branches and the number of pods per plant had a positive indirect effect on the yield at the genotypic level, suggesting that these traits could be considered for indirect selection of genotypes for yield. The genetic distances of genotypes measured by Euclidean distance ranged from 0.07 to 10.6, and the dendrogram was constructed by using the unweighted pair group method using arithmetic mean. The presence of variability among fenugreek accessions suggested possibilities to improve the crop through the crossing of distant genotypes. This was an excellent opportunity to contribute to farmers' food security and livelihoods by bringing about the improvement of fenugreek.